Mineralocorticoid Receptor Antagonism Reverses Diabetes-related Coronary Vasodilator Dysfunction: A Unique Vascular Transcriptomic Signature - Brown, Scott M. (Pharmacol Res, 2018)
Coronary microvascular dysfunction predicts and may be a proximate cause of cardiac dysfunction and mortality in diabetes; however, few effective treatments exist for these conditions. We recently demonstrated that mineralocorticoid receptor (MR) antagonism reversed cardiovascular dysfunction in early-stage obesity/insulin resistance. The mechanisms underlying this benefit of MR antagonism and its relevance in the setting of long-term obesity complications like diabetes; however, remain unclear. Thus, the present study evaluated the impact of MR antagonism on diabetes-related coronary dysfunction and defines the MR-dependent vascular transcriptome in the Otsuka Long-Evans Tokushima Fatty (OLETF) rat recapitulating later stages of human diabetes. OLETF rats were treated with spironolactone (Sp) and compared to untreated OLETF and lean Long-Evans Tokushima Otsuka rats. Sp treatment attenuated diabetes-associated adipose and cardiac inflammation/fibrosis and improved coronary endothelium-dependent vasodilation but did not alter enhanced coronary vasoconstriction, blood pressure, or metabolic parameters in OLETF rats. Further mechanistic studies using RNA deep sequencing of OLETF rat aortas revealed 157 differentially expressed genes following Sp including upregulation of genes involved in the molecular regulation of nitric oxide bioavailability (Hsp90ab1, Ahsa1, Ahsa2) as well as novel changes in α(1D) adrenergic receptors (Adra1d), cyclooxygenase-2 (Ptgs2), and modulatory factors of these pathways (Ackr3, Acsl4). Further, Ingenuity Pathway Analysis predicted inhibition of upstream inflammatory regulators by Sp and inhibition of ‘migration of endothelial cells’, ‘differentiation of smooth muscle’, and ‘angiogenesis’ biological functions by Sp in diabetes. Thus, this study is the first to define the MR-dependent vascular transcriptome underlying treatment of diabetes-related coronary microvascular dysfunction by Sp.